Tinjauan Profunditas Tentang Logika Penalaran Dan Kebenaran Dalam Filosofi - Gresia Monika Sinaga; Indri Purnama putri Harefa; Mozes Lawalata (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
When entering the realm of philosophy, logical reasoning and truth become the main foundation for critical and deep thinking. This article offers a comprehensive overview of the role and implications of both concepts in the context of philosophy. The purpose of this study is to explore the depth of the concepts of logical reasoning and truth, and identify their impact on human thought. The method applied in this study is a qualitative approach; this approach involves the systematic analysis of a wide range of literature; including the Bible, articles, books, and other sources relevant to the topic under investigation. According to Wiley, qualitative research involves the collection of actual data from a wide range of scholarly literature; which includes facts from the past and present. The scope of the study includes an exploration of different types of logical argumentation, such as deduction and induction, as well as a discussion of the nature of truth, both in absolute and relative contexts. The results highlight the importance of a deep understanding of logical reasoning in constructing strong arguments, while also illustrating the philosophical implications of the concept of truth for human views of reality. By delving deeper into these two concepts, this research provides a valuable contribution to the development of philosophical discourse and guides us towards more critical, systematic, and fact-based thinking in facing the challenges of contemporary and future thinking.